Stress–strain relationships and influence of testing parameters on coupon test results (Advances in Civil and Architectural Engineering, 2021)
Tensile steel-coupon testing qualifies as one of the more commonly used experiments for determination of basic parameters for structural design. Such tests are usually performed to determine technical stress–strain relationships of tested materials. Technical stress–strain curves are not suitable for various numerical material models that exploit the plastic region of behavior, owing to the necking effect and accompanying change in coupon area being neglected during stress determination. Material ductility is influenced by the choice of gauge length, which may cause different researchers to differently interpret coupon tests of the same material. The proposed research utilizes benefits offered by an optical system for deformation monitoring to track changes in surface area and implement them during stress calculations until fracture. The possibility of adjusting the gauge length the same sample the ability to study its effect on obtained results. Based on analyzed data, these influences were evaluated and possible errors identified.